2022
DOI: 10.1037/aca0000504
|View full text |Cite
|
Sign up to set email alerts
|

Visual perception of the built environment in virtual reality: A systematic characterization of human aesthetic experience in spaces with curved boundaries.

Abstract: Visual perception of architectural spaces and human aesthetic experience in these spaces have recently received considerable interest in cognitive science. However, it has been difficult to construe a common understanding of aesthetic experience for architectural space, since different studies use different scales to measure aesthetic experiences. In this interdisciplinary study spanning cognitive science and architecture, we aim to provide an empirically driven systematic characterization of human aesthetic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 81 publications
0
0
0
Order By: Relevance
“…Franz et al (2005) identified that architectural research can be more empirical by using VR technologies with their flexibility of stimulation and easy-to-create controlled laboratory conditions while still providing a high degree of perceptual realism. In architecture and urban research fields, more researchers have focused on VR as a medium for conducting user studies, measuring perception of space or effects of architectural elements for both users and designers by applying empirical and experimental settings recently (Elver Boz et al, 2022;Keshavarzi et al, 2021;Llorca-Bofi and V€ orlander, 2021;Zhang and Zhang, 2021;Dumlu, 2020a, b). Also, it is highlighted that VR has particular advantages with its immersive, interactive, multi-modal, multi-sensory ability to apply realworld features for neuroscience, psychology and cognitive science research (Bohil et al, 2011;Loomis et al, 1999).…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Franz et al (2005) identified that architectural research can be more empirical by using VR technologies with their flexibility of stimulation and easy-to-create controlled laboratory conditions while still providing a high degree of perceptual realism. In architecture and urban research fields, more researchers have focused on VR as a medium for conducting user studies, measuring perception of space or effects of architectural elements for both users and designers by applying empirical and experimental settings recently (Elver Boz et al, 2022;Keshavarzi et al, 2021;Llorca-Bofi and V€ orlander, 2021;Zhang and Zhang, 2021;Dumlu, 2020a, b). Also, it is highlighted that VR has particular advantages with its immersive, interactive, multi-modal, multi-sensory ability to apply realworld features for neuroscience, psychology and cognitive science research (Bohil et al, 2011;Loomis et al, 1999).…”
Section: 2mentioning
confidence: 99%
“…(2005) identified that architectural research can be more empirical by using VR technologies with their flexibility of stimulation and easy-to-create controlled laboratory conditions while still providing a high degree of perceptual realism. In architecture and urban research fields, more researchers have focused on VR as a medium for conducting user studies, measuring perception of space or effects of architectural elements for both users and designers by applying empirical and experimental settings recently (Elver Boz et al. , 2022; Keshavarzi et al.…”
Section: Research Backgroundmentioning
confidence: 99%
“…User cognition and perception at postphenomenology stage determine their level of aesthetic experience evaluated in various dimensions. While Elver Boz et al, [28], suggested that human aesthetic experience measured three key dimensions, namely familiarity, excitement, and fascination. Somehow, user must perceive beauty and art with appropriate attitude to show appreciation [42].…”
Section: Aesthetic Experiencementioning
confidence: 99%
“…In practical sense, the ideal state of virtual reality experience is evaluated after the user psychological [22,23] and phenomenological [24][25][26] experienced the virtual world, gained both immersive and aesthetic experience [26][27][28], hence felt presence [18,19], appraisal [22] and appreciate [23] the world. In short, the experience is not adequately captured by the single dimension evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, 60 participants were presented with 360-degree 32 VE visualizations that had horizontal or vertical curved boundaries and possessed various architectural properties including size, light, texture, and color, using a headmounted display and a desktop computer. The aesthetic experience was measured in terms of three key dimensions identified before (Elver Boz et al, 2022): familiarity, excitement, and fascination. In addition, participants' sense of presence was measured.…”
mentioning
confidence: 99%